Cell Type-Specific Gene Expression Analyses by RNA Sequencing Reveal Local High Nitrate-Triggered Lateral Root Initiation in Shoot-Borne Roots of Maize by Modulating Auxin-Related Cell Cycle Regulation. Issue 1 (21st July 2015) - Yu, Peng; Eggert, Kai; von Wirén, Nicolaus; Li, Chunjian; Hochholdinger, Frank
Abstract : Auxin regulates a progressive cell cycle during adult maize lateral root formation. Abstract: Plants have evolved a unique plasticity of their root system architecture to flexibly exploit heterogeneously distributed mineral elements from soil. Local high concentrations of nitrate trigger lateral root initiation in adult shoot-borne roots of maize ( Zea mays ) by increasing the frequency of early divisions of phloem pole pericycle cells. Gene expression profiling revealed that, within 12 h of local high nitrate induction, cell cycle activators ( cyclin-dependent kinases and cyclin B ) were up-regulated, whereas repressors ( Kip-related proteins ) were down-regulated in the pericycle of shoot-borne roots. In parallel, a ubiquitin protein ligase S-Phase Kinase-Associated Protein1-cullin-F-box protein S-Phase Kinase-Associated Protein 2B -related proteasome pathway participated in cell cycle control. The division of pericycle cells was preceded by increased levels of free indole-3-acetic acid in the stele, resulting in DR5-red fluorescent protein-marked auxin response maxima at the phloem poles. Moreover, laser-capture microdissection-based gene expression analyses indicated that, at the same time, a significant local high nitrate induction of the monocot-specific PIN-FORMED9 gene in phloem pole cells modulated auxin efflux to pericycle cells. Time-dependent gene expression analysis further indicated that local high nitrate availability resulted in PIN-FORMED9-mediated auxin efflux and subsequent cell cycle activation, which culminated in the initiation of lateral root primordia. This study provides unique insights into how adult maize roots translate information on heterogeneous nutrient availability into targeted root developmental responses.